A Trigger and Response System for Preventing Cardiac Arrest in the ICU - Ari Moskowitz, MD (Wolters Kluwer, 2021)
OBJECTIVES:. Although patients in the ICU are closely monitored, some ICU cardiac arrest events may be preventable. In this study, we sought to reduce the rate of cardiac arrests occurring in the ICU through a quality improvement initiative. DESIGN:. Prospective, observational study. SETTING:. ICUs of a single tertiary care center. PATIENTS:. Patients hospitalized in the ICUs between August 2017 and November 2019. INTERVENTIONS:. A comprehensive trigger and response tool. MEASUREMENT AND MAIN RESULTS:. Forty-three patients experienced an ICU cardiac arrest in the preintervention epoch (6.79 arrests per 1,000 discharges), and 59 patients experienced an ICU cardiac arrest in the intervention epoch (7.91 arrests per 1,000 discharges). In the intervention epoch, the clinical trigger and response tool was activated 106 times over a 1-year period, most commonly due to unexpected new/worsening hypotension. There was no step change in arrest rate (2.24 arrests/1,000 patients; 95% CI, –1.82 to 6.28; p = 0.28) or slope change (–0.02 slope of arrest rate; 95% CI, –0.14 to 0.11; p = 0.79) comparing the preintervention and intervention time epochs. Cardiac arrests in the preintervention epoch were more likely to be “potentially preventable” than that in the intervention epoch (25.6% vs 12.3%, respectively; odds ratio, 0.58; 95% CI, 0.20–0.88; p < 0.01). CONCLUSIONS:. A novel trigger-and-response tool did not reduce the frequency of ICU cardiac arrest. Additional investigation is needed into the optimal approach for ICU cardiac arrest prevention.